2019
DOI: 10.1002/hbm.24699
|View full text |Cite
|
Sign up to set email alerts
|

On the relevance of EEG resting theta activity for the neurophysiological dynamics underlying motor inhibitory control

Abstract: The modulation of theta frequency activity plays a major role in inhibitory control processes. However, the relevance of resting theta band activity and of the ability to spontaneously modulate this resting theta activity for neural mechanisms underlying inhibitory control is elusive. Various theoretical conceptions suggest to take these aspects into consideration. In the current study, we examine whether the strength of resting theta band activity or the ability to modulate the resting state theta activity af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 81 publications
(206 reference statements)
8
38
1
Order By: Relevance
“…Because such endogenous activity is also characteristic for resting EEG activity across different frequency bands (Hiltunen et al, 2014;Knyazev, 2013;Laufs, 2008), there may be a link between resting theta band activity and theta-based activity evident during conflict monitoring. Such a link between resting state and task-related theta activity has already been shown for motor response inhibition (Pscherer, Mückschel, Summerer, Bluschke, & Beste, 2019). A more general link between resting activity and cognitive control-related activity is suggested by studies that revealed similarities between resting neural dynamics and task-related activity from a perspective of the involved neural networks (Becker, Van de Ville, & Kleinschmidt, 2018;Tavor et al, 2016).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Because such endogenous activity is also characteristic for resting EEG activity across different frequency bands (Hiltunen et al, 2014;Knyazev, 2013;Laufs, 2008), there may be a link between resting theta band activity and theta-based activity evident during conflict monitoring. Such a link between resting state and task-related theta activity has already been shown for motor response inhibition (Pscherer, Mückschel, Summerer, Bluschke, & Beste, 2019). A more general link between resting activity and cognitive control-related activity is suggested by studies that revealed similarities between resting neural dynamics and task-related activity from a perspective of the involved neural networks (Becker, Van de Ville, & Kleinschmidt, 2018;Tavor et al, 2016).…”
mentioning
confidence: 67%
“…In the current study, we examined the strength of the association between resting theta band activity and conflict-related neurophysiological activity. In a previous study, we have already shown that resting theta activity is related to task-related theta activity during motor response inhibition (Pscherer et al, 2019). Unlike these previous data (Pscherer et al, 2019), we here focus on conflict monitoring (or interference control), which is different from motor inhibition processes, even though some inhibitory control aspect has also been discussed for the control of conflicting sensory information (Chmielewski, Mückschel, Roessner, & Beste, 2014;Klein, Petitjean, Olivier, & Duque, 2014;Ocklenburg, Güntürkün, & Beste, 2011;Stürmer, Siggelkow, Dengler, & Leuthold, 2000;Tandonnet, Garry, & Summers, 2011;Verleger, Kuniecki, Möller, Fritzmannova, & Siebner, 2009).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Like the ACC, this structure is well-known to be modulated by alcohol. Medial frontal theta oscillations originating in these mid-frontal brain regions have been shown to reflect cognitive control processes, including response inhibition [21,[89][90][91]. The SMA is considered to play a key role in stopping a response [29].…”
Section: Discussionmentioning
confidence: 99%